The Evolution of Free Radical Biochemistry in Historical Perspective - ÇAKATAY, Ufuk; KAYALI, Refik (Cerrahpaşa Medical Journal, 2014)
The existence of free radicals, as chemical entities, was inferred 100 years ago but not universally accepted for nearly 40 years. The existence and importance of free radicals in biological systems was not recognized until the mid 1950’s, by a small number of visionary scientists who can be credited with founding the field of reactive oxygen biochemistry. For most of the remaining 20th century, reactive oxygen species (ROS) were considered a type of biochemical “rusting agent” that caused tissue damage and disease. As we enter 21st century, reactive oxygen biochemistry is maturing as a discipline and establishing its importance among the biomedical sciences. It is now recognized that virtually every disease state involves some degree of oxidative stress. Moreover, we are now beginning to recognize that ROS are produced in a well-regulated manner to help maintain homeostasis on the cellular level in normal, healthy tissue. Emerging technologies, particularly proteomic technologies are discussed in scientific community that will facilitate further evolution in the field of free radical biochemistry.